2004
DOI: 10.1016/s0002-9440(10)63405-0
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Topography of Neuronal Aβ Peptide in APPxPS1 Transgenic Mice

Abstract: In transgenic mice expressing human mutant beta-amyloid precursor protein (APP) and mutant presenilin-1 (PS1), Abeta antibodies labeled granules, about 1 microm in diameter, in the perikaryon of neurons clustered in the isocortex, hippocampus, amygdala, thalamus, and brainstem. The granules were present before the onset of Abeta deposits; their number increased up to 9 months and decreased in 15-month-old animals. They were immunostained by antibodies against Abeta 40, Abeta 42, and APP C-terminal region. In d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
102
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 68 publications
20
102
1
2
Order By: Relevance
“…Moreover, immunogold labeling of N2a cells with an anti-A␤ antibody showed that A␤ peptides also were localized to MVBs (Fig. 3), consistent with previous reports (29,30). Proteins that are destined for lysosomal degradation are sorted from the early endosomes to intraluminal vesicles of the MVBs or late endosomes.…”
Section: A Fraction Of A␤ Peptides Is Localized To Mvbs and Is Releassupporting
confidence: 90%
“…Moreover, immunogold labeling of N2a cells with an anti-A␤ antibody showed that A␤ peptides also were localized to MVBs (Fig. 3), consistent with previous reports (29,30). Proteins that are destined for lysosomal degradation are sorted from the early endosomes to intraluminal vesicles of the MVBs or late endosomes.…”
Section: A Fraction Of A␤ Peptides Is Localized To Mvbs and Is Releassupporting
confidence: 90%
“…Specifically, it reconciles the known extracellular deposition of terminal amyloid plaques in AD patients or AD mouse models (15, 23) with numerous observations from AD patients (33), AD mouse models (34) and Aβ-transgenic Drosophila melanogaster flies (35) showing that Aβ species may also accumulate inside the cell, including MVBs (16,36,37), lysosomes or other vesicular compartments (38)(39)(40). The present observation of an intracellular route of amyloid plaque formation is consistent with observations that extracellular amyloid plaques typically contain a spectrum of proteins that are originally intracellular.…”
Section: Discussionsupporting
confidence: 52%
“…The present observation of an intracellular route of amyloid plaque formation is consistent with observations that extracellular amyloid plaques typically contain a spectrum of proteins that are originally intracellular. For instance, AD plaques commonly contain lysosomal proteases or molecular chaperones from the heat shock protein families Hsp70 or Hsp20 (17,36,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…29). Several APP derivatives accumulate in multivesicular bodies (MVBs), in transgenic animal models of amyloidosis (30,31), in Alzheimer disease (30), and in cell models (32). MVBs belong to the endocytic pathway (33); are at the crossroad of several cellular mechanisms such as membrane receptor recycling and protein degradation; and can release their intraluminal vesicles, known as exosomes (for review, see Refs.…”
mentioning
confidence: 99%